American Black Duck Nesting Ecology in North Carolina. Issue 5 (6th May 2021) - Lawson, Daniel M.; Williams, Christopher K.; Howell, Douglas L.; Fuller, Joseph C.
ABSTRACT: North Carolina, USA, is the southernmost extent of the American black duck's ( Anas rubripes ) breeding range; however, little is known about their nesting ecology in this region. We located and monitored 140 nesting black ducks over 2 years (2017–2018) to quantify preferred nesting habitat and assess nesting productivity within coastal North Carolina. We located nests in brackish marshes (75%) and man‐made dredge spoil islands (25%) at a density of 1 nest/22 ha. Black ducks selected high marsh and nested an average of 21.81 m from open water at a mean elevation of 1.36 m. In preferred nesting habitat, visual obstruction readings were 0.50 m with a maximum mean vegetation height of 0.81 m and land cover consisted largely of grasses (84.6%). Apparent nest success rates varied from 31% (2017) to 63% (2018) across years. The majority (72.2%) of variability in nest success was best predicted by nest location (mainland marsh, natural island, or spoil island), vegetation density, maximum vegetation height, and year. Management for breeding black ducks in coastal North Carolina should focus on promoting selected nesting habitat and reducing nest predators. Prescribed burns, used to set back succession on spoil islands and in brackish marshes should be conducted in the winter or in the early growing season not to exceed the twenty‐fifth quantile date of black duck nest initiation (2 Apr). © 2021 The Wildlife Society. : American black duck nesting productivity at the southernmost extent of their range is modeled best by nest‐site location (mainland marsh, natural island, or spoil island), vegetation density, maximum vegetation height, year, and nest initiation date and most influenced by small‐mammal depredations and to a lesser extent spring flooding. Future conservation and management efforts of black ducks in coastal North Carolina will benefit from the maintenance of natural islands and spoil islands, where predation pressure is the lowest and nests are less prone to spring flooding.